Analysis of Factors Causing Air Pollution on Ships - San Maulina Sihaloho; Fitria Saftarina; Sudjarwo MA (International Journal Labs, 2023)
Air pollution on ships is a serious problem that can affect human health, the environment, and the operational safety of the ship itself. The aim of this study is to identify and understand the factors that contribute to air pollution on ships, as well as provide a better understanding of its impact on human health and the environment. This study used the research method of literature review. Data collection techniques are carried out by literature studies, data obtained through Google Schoolar. The results showed that poor air quality inside the ship can be caused by exhaust emissions from the engine, inefficient fuel use, the presence of an inadequate exhaust gas separation system, shipping in traffic-heavy areas or routes often used by large ships, fuel combustion processes, and weather factors. The impact of air pollution on human health includes respiratory disorders, cardiovascular disorders, to skin health problems. While the impact on the environment includes air pollution in the port area, water pollution, and soil pollution.